Towards Sustainable Open Heart Surgery in Zimbabwe - Machawira, Simukayi Percy; Muteweye, Wilfred; Mutetwa, Emmerson; Kajese, Shield (Frontiers in Pediatrics, 2022)
Open heart surgery has become more readily available worldwide, especially in the West, whilst it remains elusive for the majority of the people in Sub-Saharan Africa, and Zimbabwe in particular. Efforts to provide the service began in the 1950s and open heart surgery became a regular service from 1989 to 2003. From 1997, Zimbabwe went through a phase of political and economic turmoil resulting in the disruption of meaningful service. This study seeks to make the case for prioritization of domestic resources toward open heart surgery, taken as learning from African countries that faced a similar predicament such as Ghana but who have since been able to sustain their programs. To ensure the success of the program, the following are necessary: the requisite personnel, equipment, consumables, and competitive remuneration. The plan is to work with Government, the private sector, and other players to harness resources toward sustainable open heart surgery in Zimbabwe.